Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV SONNE during cruise SO196 - Gregor Rehder; Jens Schneider von Deimling (PANGAEA, 2025)
Multibeam bathymetry raw data using the ship extquotesingles own Kongsberg (Simrad) EM 120 multibeam echosounder was not continuously recorded during RV SONNE cruise SO196. Data was recorded on 17 days between 2008-03-06 and 2008-03-22. This dataset contains a survey in the East China Sea. The approximate average depth of the entire dataset is around 1400m. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. One ancillary sound velocity profiles (SVP) files from the cruise is archived at the BSH and added to this dataset. Data analysis of the multibeam raw data revealed that SVP has been changed one time during the survey, however the SVP origin is unknown. This publication is conducted within the efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality is rather good since the gridded hillshade data showed relatively few obstacles. Data can be processed e.g. with the open source software package MB-System (Caress et al. 2024, https://doi.org/10.5281/zenodo.6302801).